Construction of Community Perceptions on Government Effort in Managing the Covid-19 Pandemic: A Covid Score-10 Approach - Irwan Soejanto; Intan Berlianty; Nur Prangawayu (Applied Quantitative Analysis, 2022)
Countries worldwide are still struggling to deal with the spread of COVID-19.  No country in the World has been able to get out of the pandemic yet.  The number of patients dying, recovering and getting sick shows a graph of increasing every day.  To stop the spread of COVID-19 requires uniformity and support from the community. The expected result of this study is to know and construct knowledge, perceptions, and attitudes of the community towards the Covid-19 handling program that has been and will be carried out by the government. The research method uses a quantitative descriptive approach to Covid-10 with an online survey method using a questionnaire provided in the form of a google form application. Data collection was carried out by stratified random sampling and disseminated through the media with a sample of 1,191 respondents in the DIY Region. Most respondents (95.1%) supported the government's efforts to change behavior in the face of the pandemic. However, 42.1% of respondents felt the government had created the right programs and policies.